The efforts of the Madrasah Principal to Improve the Quality of Islamic Education Post of the Natural Disaster in Palu City - Risman, Risman; S. Pettalongi, Sagaf; Saude, Saude (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2023)
This research discusses the efforts of the madrasah principal to improve the quality of Islamic education after the 2018 disaster. This research aims to examine the actions of the madrasah principal in improving the quality of Islamic education and identify the supporting and inhibiting factors faced by the madrasah principal in improving the quality of Islamic education after the 2018 natural disaster. This research uses a qualitative method with a descriptive approach. The study was conducted at State Islamic Senior High School 1 Palu. Data were collected through direct observation, in-depth interviews, and written documents. The results of this research show that the efforts made by the madrasah principal in improving the quality of Islamic education after the natural disaster include improving the quality of education and teaching, collaborating in the field of human resources, implementing education following the madrasah's vision and mission, maximizing the use of existing facilities and infrastructure, and proposing the construction of a building to the government and donors. Several factors that support the madrasah principal's efforts include the collaboration between the madrasah principal, teachers, educational staff, parents, and the community in achieving the goals of the madrasah principal.